Marfan Syndrome: A Case Report - Rob Mahmud, Mohammad Golam (Jalalabad Medical Journal, 2025)
Marfan syndrome is a rare autosomal dominant, multisystem connective tissue disease, caused by mutation in the extra cellular matrix protein fibrillin-1 gene located on chromosome 15. It has variable phenotypic expression with a reported incidence of 1 in 3000 to 5000 individuals. There is a wide range of clinical severity associated with Marfan syndrome with classic ocular, cardiovascular and musculo-skeletal abnormalities. The diagnosis of Marfan syndrome relies essentially on the fulfilment of clinical diagnostic criteria. We report a case of an 18 years old male with positive family history including lean and thin body stature, joint hypermobility, high arched palate, pectus excavatum, total arm span more than total body height (1.11:1), lower segment greater than upper segment (1.34:1) and mitral valve prolapse. Jalalabad Med J 2023; 20 (1): 31-34